2020
DOI: 10.3390/agriculture10120616
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and Biometric Characteristics of 11 Varieties of Willow Cultivated on Marginal Soil

Abstract: In response to the growth in the global population and climate change concerns, questions remain regarding the adaptation of production systems to meet increasing food and energy demands. The aim of the paper is to present the production potential and biometric features of 11 willow varieties bred and cultivated mainly in Europe. The experiment was set up on marginal soil. The research was conducted in 2016–2020 and concerned 11 varieties of willow harvested in a three-year cycle. The dry matter yield of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Only 10 presented information related to both clones, while 14 were associated with Inger and 18 with Tordis. Most research was focused on yield, dry biomass, management, and fertilizers in field conditions [50,[82][83][84][85][86][87], and there were only a few studies on harsh conditions [31,37,38,[88][89][90][91]. In both contexts, a short pre-field experiment was useful to establish and promote the rhizogenesis potential of willow clones by recreating the nutritional conditions of the planting site and recording the plant growth and development parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 10 presented information related to both clones, while 14 were associated with Inger and 18 with Tordis. Most research was focused on yield, dry biomass, management, and fertilizers in field conditions [50,[82][83][84][85][86][87], and there were only a few studies on harsh conditions [31,37,38,[88][89][90][91]. In both contexts, a short pre-field experiment was useful to establish and promote the rhizogenesis potential of willow clones by recreating the nutritional conditions of the planting site and recording the plant growth and development parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been carried out on various willow hybrids [26][27][28][29][30][31]. In Romania, and at an international level, several problems with rooting, attachment, and the juvenile stages of willow cuttings were highlighted [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…It requires the minimum amount of nutrients and its cultivation is perceived as an advantageous way to use soils of low usability for food crop growing [60]. Willow can be grown on many types of agricultural land as it is highly tolerant of environmental conditions, with wetlands being preferred for this purpose [61][62][63]. Szczukowski et al [64] demonstrated the potential for willow biomass production on excessively damp soil with a high groundwater table level.…”
Section: Biomass From Perennial Energy Cropsmentioning
confidence: 99%
“…The food processing industry is also a source of biomass for energy generation, both as solid biofuels and feedstock for biogas production. Agriculture can also provide solid biofuels from plantations of perennial industrial crops, which is particularly interesting when such plantations are set up on marginal soil [7][8][9][10][11]. However, straw is now the main type of solid biomass derived from agriculture.…”
Section: Introductionmentioning
confidence: 99%